2014
DOI: 10.1155/2014/307421
|View full text |Cite
|
Sign up to set email alerts
|

Sauna-Induced Body Mass Loss in Young Sedentary Women and Men

Abstract: The aim of the study was to evaluate the relationship between body mass index (BMI) and body mass loss (BML) induced by thermal stress in a dry sauna. The study was conducted on a group of 674 sedentary students, 326 women and 348 men aged 19-20. The correlations between BMI scores and BML were determined. The subjects were placed in supine position in a dry sauna for two sessions of 10 minutes each with a 5-minute break. The influence of BMI on the amount of BML in the sauna was determined by nonlinear stepwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
(41 reference statements)
3
15
0
Order By: Relevance
“…The physiological systems most impacted by sauna sessions are the skin and the thermoregulatory and cardiovascular systems [ 8 ]. Despite a normal strong response of the thermoregulatory system, involving an increased production of sweat, internal body temperature typically increases during a dry sauna.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological systems most impacted by sauna sessions are the skin and the thermoregulatory and cardiovascular systems [ 8 ]. Despite a normal strong response of the thermoregulatory system, involving an increased production of sweat, internal body temperature typically increases during a dry sauna.…”
Section: Introductionmentioning
confidence: 99%
“…The similar results were reported demonstrating that 0.48%-0.92% weight reduction was observed after dry sauna bathing (temperature 90°C, humidity 35%) for two sessions for 10 minutes each with a 5-minutes break. 18 Another group has investigated body weight changes pre-and postsauna bathing. 17 Although statistically significant weight reduction was seen upon sauna therapies in those studies, the weight reduction observed was only to lesser extent (averagely <0.5 kg).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…All called examples having an influence on control of nerves conduction and, the same on reactivity, find reference in results interpretation and probably this is why do not find any confirmation in publication in which the author says that under the higher body temperature activity of gamma motoneurons and skeletal muscles fibres activation decline. In consequence activity of alfa motoneurons is decreased what results in weaker muscle tension and skeletal muscle relaxation (Prystupa et al, 2009;Podstawski et al, 2015;Mero et al, 2015;Sawatari et al, 2015).…”
Section: Discussionmentioning
confidence: 99%